Comet candidates among quasi-Hilda objects - Gil-Hutton, Ricardo (2016)
We present the results of a search for quasi-Hilda comets. We wanted to find objects that have recently arrived from the Centaur zone that could became active near the perihelion of their orbits. Methods. Two hundred and seventy-seven objects from the ASTORB database were selected following a dynamical criteria to constrain the unstable quasi-Hilda region. These objects were integrated backward 50 000 yr in order to identify those that have recently arrived from the outer regions of the solar system. Results. The backward integration showed that 11 objects could be Centaurs or transneptunian objects that ended their dynamical evolution as quasi-Hilda comets. The dynamical evolution of these objects from a statistical point of view was studied by computing the time-averaged distribution of a number of clones as a function of the aphelion and perihelion distances. All the candidates show a dynamical behavior that is expected for comets injected in the inner solar system from the Centaur or transneptunian regions and reaching the quasi-Hilda region.